Hybrid of conical and spiral approach for wireless power transfer - Nataraj, Chandrasekharan; Khan, Sheroz; Habaebi, Mohamed Hadi; Abdul Muthalif, Asan Gani; Naidu, Djaiprakash; Selvaperumal, Sathish Kumar (IEEE, 2017)
This paper presents the new coil design strategy for Wireless Power Transfer (WPT) applications. In order to produce better power transfer efficiency for remotely located load, hybrid approach is proposed using two different coils such as conical and spiral. Hybrid approach refers the coil model by engaging conical as a transmitter and spiral as a receiver in a single system. The field pattern of conical coil is cumulative so that better magnetic field is possible at the bottom side for high directivity. In contrast, the spiral coil produces distributive field pattern so that the field distribution is uniform. Taking advantage of these two different behaviors, better power efficiency would be achieved by reducing power loss in the coil zone. For this hybrid approach, Finite Element Method (FEM) based conical and spiral coils were developed and simulated to determine field patterns and their value. Two different prototypes (Conical and spiral) were experimented with fixed spiral load coil to validate the performance of the hybrid approach. The output load coil voltage and efficiency plots were made based on the measurement, for analyzing the system performance. It is recorded the efficiency of 72% with the optimum distance 10cm and biasing voltage 10V respectively. The results from simulation as well as experiment confirms that hybrid approach could support significantly to reduce power loss and increase the relative operative distance.